Kepraktisan dan Keefektifan Handout Populasi Tumbuhan Hutan Pantai Tabanio Sebagai Materi Pengayaan Mata Kuliah Ekologi Tumbuhan - Dharmono Dharmono; Maulana Khalid Riefani (Program of Biology Education, Universitas Lambung Mangkurat, 2019)
One of the causes of learning difficulties in the population concept is that there are not many locally-based materials. The purpose of this study was to obtain a Handout of Plant Populations of the Tabanio Coastal Forest as a practical and effective Plant Ecology Enrichment Course. This research is a development research using Education Design Research (EDR) design through formative evaluation of the Tessmer model at the small group test stage to determine the practicality of expectations and the effectiveness of expectations from the developed Handout. The subjects of this study were 10 students of the Biology Education Study Program, FKIP University of Lambung Mangkurat Banjarmasin with the object of research being plant population structures found in the coastal forest of Tabanio, Tanah Laut Regency. The results of the research show that the teaching materials in the form of handouts developed are very practical and very effective to be used as material for enriching the population concept in improving learning outcomes for the Plant Ecology course.